1977
DOI: 10.1136/jnnp.40.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and papilloedema in the Guillain-Barre syndrome.

Abstract: SUMMARY Three patients with the Guillain-Barre Syndrome are described, one of whom was relapsing. Hypertension persisted for three to four months in two patients, associated with increased urinary excretion of catecholamines. Baroreceptor sensitivity, although depressed, did not explain the hypertension. It may be due to lesions affecting either central vasomotor control or peripheral sympathetic nerve activity. Two patients had papilloedema. This has been attributed in the literature to defective reabsorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 16 publications
1
7
1
1
Order By: Relevance
“…14 23 The method has been used to demonstrate impairment of baroreflex sensitivity in patients with diabetic neuropathy.29 It is simpler than that devised by Korner et al,14 which measures the steady state characteristics of the baroreflex and which has been used previously in our laboratory.7 8 Lesions in the afferent nerve fibres in the glossopharyngeal and vagus nerves from the carotid sinus and aortic arch baroreceptors and/or efferent fibres in the vagus nerves may reduce the sensitivity of the baroreflex which was found in four of the patients in the present study and in the patient of Davidson and Jellinek. 28 The glossopharyngeal and vagus nerves are known to be affected both clinically6 and pathologically30 in Guillain-Barre syndrome although in the present study only one (Case 5) of the four patients with an abnormal baroreceptor heart rate reflex had obvious clinical evidence of involvement of these cranial nerves.…”
Section: Discussioncontrasting
confidence: 48%
“…14 23 The method has been used to demonstrate impairment of baroreflex sensitivity in patients with diabetic neuropathy.29 It is simpler than that devised by Korner et al,14 which measures the steady state characteristics of the baroreflex and which has been used previously in our laboratory.7 8 Lesions in the afferent nerve fibres in the glossopharyngeal and vagus nerves from the carotid sinus and aortic arch baroreceptors and/or efferent fibres in the vagus nerves may reduce the sensitivity of the baroreflex which was found in four of the patients in the present study and in the patient of Davidson and Jellinek. 28 The glossopharyngeal and vagus nerves are known to be affected both clinically6 and pathologically30 in Guillain-Barre syndrome although in the present study only one (Case 5) of the four patients with an abnormal baroreceptor heart rate reflex had obvious clinical evidence of involvement of these cranial nerves.…”
Section: Discussioncontrasting
confidence: 48%
“…3 Optic nerve involvement has been described in acute inflammatory demyelinating polyneuropathy, but no association has been reported with the axonal motor variant. 4,5 We report the clinical, immunologic, and longitudinal electrophysiological findings in a 56-year-old white man with acute, purely motor polyneuropathy, who subsequently developed bilateral visual field loss secondary to bilateral papillitis. Another peculiar clinical feature was hyperreflexia at the time of diagnosis, when moderate paresis of his limbs was already present.…”
Section: Introductionmentioning
confidence: 99%
“…These cardiovascular symptoms may be serious or even fatal during the clinical course, as they take the form of either excessive or inadequate activity of the sympathetic and/or parasympathetic systems (3). Concerning autonomic cardiovascular dysfunction, according to the findings of physiological and endocrinological examinations, GBS patients with hypertension and tachycardia in the acute phase are considered to have cardiac sympathetic hyperactivity (8)(9)(10)(11). On the electrophysiological examination, it was confirmed that the patients had cardiac sympathetic hyperactivity and overactivity (12).…”
Section: Discussionmentioning
confidence: 98%